The Effectiveness of Project-Based Learning Assisted by Digital Technology to Improve Problem-Solving and Critical Thinking Skills in SMKN 3 Sampang Students - Mabrur Mabrur; Nuril Huda; Sri Utami (Jurnal Indonesia Sosial Sains, 2024)
Lack of students' ability to find idols that reflect national values ​​and weak vision of their future. Technology-based PjBL learning is applied to engage students in active and collaborative learning processes, helping them develop critical thinking and problem-solving skills. This study aims to analyse the effectiveness of project-based learning (PjBL) supported by digital technology in improving students' critical thinking and problem-solving skills at SMKN 3 Sampang. This study is a quantitative study with a positivist approach. A descriptive survey approach examines variables and research units without considering the relationship between variables. The results show that this method is effective in improving these skills and motivating students to be more involved in learning, with environmental support playing an important role in optimizing results. In conclusion, innovation in learning methods that are adjusted to technological developments and the needs of the world of work is needed to ensure that vocational high school graduates have adequate competencies and are relevant to industry demands.